Kisspeptin induces LH release and ovulation in an induced ovulator. Issue 1 (20th April 2020) - Carrasco, Rodrigo A; Leonardi, Carlos E; Hutt, Kylie; Singh, Jaswant; Adams, Gregg P
Abstract: Kisspeptin has been implicated in the ovulatory process of several species of spontaneous ovulators but in only one induced ovulator. In contrast, NGF in semen is the principal trigger of ovulation in other species of induced ovulators—camelids. We tested the hypotheses that kisspeptin induces luteinizing hormone (LH) secretion in llamas through a hypothalamic mechanism, and kisspeptin neurons are the target of NGF in its ovulation-inducing pathway. In Experiment 1, llamas were given either NGF, kisspeptin, or saline intravenously, and LH secretion and ovulation were compared among groups. All llamas treated with NGF (5/5) or kisspeptin (5/5) had an elevation of LH blood concentrations after treatment and ovulated, whereas none of the saline group did (0/5). In Experiment 2, llamas were either pretreated with a gonadotropin-releasing hormone (GnRH) receptor antagonist or saline and treated 2 h later with kisspeptin. Llamas pretreated with saline had elevated plasma LH concentrations and ovulated (6/6) whereas llamas pretreated with cetrorelix did not (0/6). In Experiment 3, we evaluated the hypothalamic kisspeptin-GnRH neuronal network by immunohistochemistry. Kisspeptin neurons were detected in the arcuate nucleus, the preoptic area, and the anterior hypothalamus, establishing synaptic contacts with GnRH neurons. We found no colocalization between kisspeptin and NGF receptors by double immunofluorescence. Functional and morphological findings support the concept that kisspeptin is a mediator of the LH secretory pathway in llamas; however, the role of kisspeptins in the NGF ovulation-inducing pathway in camelids remains unclear since NGF receptors were not detected in kisspeptin neurons in the hypothalamus. Abstract : Kisspeptin induces LH secretion and ovulation in llamas.